Implementation of IPv6 network testbed: Intrusion detection system on transition mechanism - Bahaman, Nazrulazhar; Anton Satria, Prabuwono; Mas'ud, Mohd Zaki (Asian Network for Scientific Information, 2011)
The potential of internet protocol version 6 (IPv6) cannot be denied as compared to the current network protocol (IPv4). The IPv6 ability which is offering huge amount of IP addresses has makes it being awaited by the Internet user. To make the IPv6 implementation successfully, a transition mechanism is needed to simplify the migration process between IPv4 to IPv6. The transition mechanism is created to support the joint operation between these protocols. However, after several years of implementation, it is believed that this mechanism has become an alternative route for intruders and attackers to penetrate the existing network. The problem kept remains without even being detected by any detection tools. Based on this problem, this study proposed an IPv6 network testbed for dealing with designation and implementation of Intrusion Detection System (IDS) on transition mechanism environment. All the equipments, tools and network are configured based on real process of transmitting IPv6 packets over IPv4 network. With fully functional operation for handling basic transition between IPv6 clients over IPv4 networks and equipped with intrusion detection tools, the testbed is used for investigating the intrusion activities behavior on the transition mechanism in the real environment. The result obtained from the testing phase shows the efficiency and the functionality of all hardware and software used. Moreover, the implementation of the testbed is expected to contribute to the realization of IPv6. Â© 2011 Asian Network for Scientific Information.